The Influence of General Facilities, General Service, Registration Service, Service Providers and Accessibility on Patient Satisfaction of Antenatal Care at XYZ Hospital - Putrantika, Angky Purbo; Dewi Sri Surya Wuisan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The aim of this research is to examine and analyze the influence of public facilities, public services, service providers and accessibility on patient satisfaction with antenatal services at XYZ Hospital. Testing of the modified research model from previous research was carried out using data from midwifery services at the hospital. The method in this research is a quantitative approach with surveys and cross sectional. Respondent data was taken in 2024 by purposive sampling with questionnaires from individuals who had received antenatal care services at XYZ Hospital. There are 180 samples that meet the requirements described by PLS-SEM. The results of this research show that the five variables are proven to have a significant and positive influence. This research adds a contribution that focuses more on antenatal care services in hospitals. It is recommended in future research to include more hospitals of various types and a larger sample size so that the analysis results can be more generalized at the population level. Future research is recommended to consider adding other variables that may potentially influence patient satisfaction.